اسلام میں عبادت کا تصور اور اس کے مقاصد : The concept of worship in Islam and its Objectives - Dr. Shazia; Sania Nawaz (Al Manhal Research Journal, 2025)
Abstract In Islam, the concept of worship holds fundamental significance, serving as a means to strengthen the bond between humans and their Creator, attain spiritual tranquility, and enhance moral and social life. Worship is not limited to specific acts or rituals; rather, it is a comprehensive concept that encompasses every aspect of life. This study highlights the Qur’anic and Prophetic understanding of worship and explores its various dimensions, such as prayer, fasting, almsgiving, pilgrimage, and other virtuous deeds, emphasizing their positive impacts on both individual and collective life. Furthermore, the objectives of worship, such as seeking Allah’s pleasure, achieving piety, and serving humanity, are also discussed. The aim of this study is to clarify the broad and practical aspects of worship, enabling a deeper understanding of Islamic teachings.